PELAKSANAAN SANKSI PIDANA PEMBAYARAN UANG PENGGANTI TERHADAP KORPORASI DALAM TINDAK PIDANA KORUPSI: PELAKSANAAN SANKSI PIDANA PEMBAYARAN UANG PENGGANTI TERHADAP KORPORASI DALAM TINDAK PIDANA KORUPSI - siregar, deny setiawan; Ablisar, Madiasa; Yunara, Edi (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2023)
Abstract; In law enforcement practices in the country, Law Enforcers, especially Judges, still have not made the right decision, that is, there is an imbalance between the expected legal aspects (das sollen) and aspects of law enforcement in society (das sein), giving rise to problems related to the determination of criminal responsibility defendants who can also be charged to corporations as well as the unclear purpose of paying compensation money, whether to seize assets resulting from corruption or to compensate for state losses. The research method used in this manuscript is normative legal research, namely by case studies and also taking or collecting data with various kinds of references contained in the literature either through reading books, laws and regulations, articles and other existing reference sources. relationship with this material. Based on the results of the research, it can be concluded that in order to solve the problems faced, the Supreme Court of the Republic of Indonesia and the Attorney General’s Office of the Republic of Indonesia. make regulations that can serve as guidelines for law enforcers in determining corporate criminal responsibility and determining the amount of reimbursement of money that is as much as possible equal to the property obtained from criminal acts of corruption and not merely the amount of state losses caused. As for the advice given by the author, namely the need to reform the Criminal Code and the Criminal Procedure Code by emphasizing corporations as legal subjects that can be held criminally responsible, because of the existence of regulations of the Supreme Court of the Republic of Indonesia. and Regulation of the Attorney General of R.I. it has limitations in regulating the handling of criminal acts committed by corporations, namely in certain cases it is prohibited to regulate more than what has been stipulated by law. Keywords; Corporate criminal responsibility, the payment of compensation money against corporations, criminal acts of corruption